A simple tool to evaluate the effectiveness of HIV care for settings with gaps in data availability (ESTIHIV) - Dorthe Raben; Marie L. Jakobsen; Jamina Trajanovska; Justyna Kowalska; Anna Vassilenko; Snezana Dragas; Arjan Harxhi; Gordana Dragovic; Nadine J. Jaschinski; Bastian Neesgaard; Klaus Hjorth-Larsen; Harmony Garges; et al. (PLoS ONE, 2025)
Many HIV clinics with poor IT-infrastructure are unable to report data on individuals in care with HIV, on antiretroviral treatment (ART) and virologically suppressed (VS), with the aim of monitoring the HIV Continuum of Care to estimate efficacy of HIV treatment programmes. We developed an estimation-tool, ESTIHIV, and determined the minimal data required for a random sample, to produce representative estimates, with a specified level of precision, of people with HIV on ART and VS. For proof of concept, 8852 HIV positive persons from seven clinics in seven different countries, with a follow-up visit during 2017, were included. Of those, 93.8% were on ART (95% CI 93.3–94.2) and 76.7% were VS (95% CI 75.8–77.6). In 2022, we tested the tool in the RESPOND Cohort for all countries with more than 100 participants under follow-up in 2019. We included 26,426 HIV positive persons from clinics in 27 countries, 97.8% (95% CI 97.6-98.0) were on ART and 91.5% were VS (95% CI 91.2-91.8%). There was good agreement between the RESPOND country estimates of ART and VS and the estimations using a random sample calculated in ESTIHIV. With ESTIHIV, clinics can produce a reliable estimate in figures for reporting and for monitoring the effectiveness of care in their clinics.